PENGARUH GAYA HIDUP, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA MANOS COFFEE - Fungky Arsana, I Komang; Prawitasari, Putu Putri; Raka Suardana, Ida Bagus; Lestara Permana, Gusi Putu (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of lifestyle, price, and product quality partially and simultaneously on purchasing decisions. The sample in this study is 112 Manos Coffeee consumers. The data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, the results were obtained that lifestyle has a positive and significant effect on purchase decisions, price has a positive and significant effect on purchase decisions, product quality has a significant positive effect on purchase decisions and lifestyle, price and product quality have a significant effect on purchase decisions. The magnitude of the influence of independent variables on purchase decisions was 57.3%. The suggestion that researchers can give is that Manos Coffee should make the design of a more comfortable place, make innovations so that later have products that are superior to competitors, make food and beverage displays more attractive, and always try to make products that are superior to competitors.